Yeni Bir İhtilâcnâme - Seğirnâme Nüshası / A New ihtilâcnâme - Seğirnâme Manuscript - Yalap, Hakan (Journal of History Culture and Art Research, 2017)
Abstract For mankind, the feeling of knowing beyond the moment has always been a matter of curiosity. For this reason, it can be seen that fortune and kinds of fortune are constant and influential in all cultures. Therefore, in literature, literary forms are found around the concept of "fortune". The fortune book Irk Bitig written in Gokturk letters is the earliest known document of this type. Twitching is an uncontrollable movement which may occur somewhat part of the body, that is the muscles beneath the skin move slightly with the skin. The works taken on the basis of the interpretations made on the basis of twitching any of the organs of the human body are called seğirnâme or ihtilâcnâme. Seğirnâme’s, which were dated to ancient times in Turkish culture and Turkish literature, have an important place for the history of literature and language. There have been many studies on these types of manuscripts in Turkey and in the world’s libraries. When the studies are examined, it has been seen that the texts of seğirrnâme texts are mostly prose texts, but there are also verse texts. In this work, which is based on a self-contained manuscript in the Library of the University of Leipzig, the work on public works was evaluated and the text was transcribed into the transcription alphabet and the language and spelling characteristics were examined. The text in which 139 twitches are involved can be considered voluminous. As a result of the new academic studies from seğirnâme manuscripts to be carried out after that, a more detailed informations about the type of seğirnâme’s, the contents of the languages and language features will be reached. Öz İnsanoğlu için bulunduğu anın ötesini bilme ve ötesinde yaşama hissi her dönem etkili olmuştur. Bu sebeple tüm kültürlerde fal ve fal türlerine ilginin sürekli ve etkili olduğu görülebilir. Dolayısıyla edebiyatta “fal” kavramı etrafında şekillenmiş edebî türlere rastlanmaktadır. Göktürk harfleri ile yazılmış olan Irk Bitig adlı fal kitabı bu türün şimdilik bilinen en eski belgesidir. Seğirmek, vücudun bir yerinde deri ile birlikte derinin hemen altındaki kasların hafifçe oynamasıdır. İnsan bedeninin herhangi bir organının seğirmesine dayanılarak yapılan yorumlar neticesinde kaleme alınan eserlere seğirnâme veya ihtilâcnâme adı verilir. Türk kültüründe ve Türk edebiyatında çok eski dönemlere tarihlenen seğirnâmeler edebiyat ve dil tarihi için önemli bir yere sahiptir. Türkiye ve dünya kütüphanelerinde pek çok yazma nüshası olan bu türler hakkında çalışmalar yapılmıştır. Yapılan çalışmalar incelendiğinde seğirnâme metinlerinin çoğunlukla mensur metinler olduğu, ancak manzum seğirnâmelerin de bulunduğu görülmüştür. Leibzig Üniversitesi Kütüphanesindeki müstakil bir yazma nüshaya dayanan bu çalışmada umumi olarak seğirnâmeler üzerine yapılan yayınlar değerlendirilerek metin transkribe edilmiş, dil ve imlâ özellikleri incelenmeye çalışılmıştır. 139 seğirmenin yer aldığı metin, bu hâliyle hacimli sayılabilir. Yeni seğirnâme nüshaları üzerinden bundan sonra yapılacak akademik çalışmalar neticesinde seğirnâme türü, seğirnâmelerin içeriği ve dil özellikleri hakkında daha etraflı bilgilere ulaşılacaktır.